Evaluación de la calidad docente en la inclusión educativa del alumnado con Trastorno del Espectro Autista: un análisis comparado entre España y Portugal (Revista Lusófona de Educação, 2026)
Educational inclusion of students with ASD in Spain and Portugal: educational policies, teacher support and comparative perspectivesAbstractThe educational inclusion of students with Autism Spectrum Disorder (ASD) is one of the greatest challenges facing contemporary education systems and a key indicator of their quality and equity. This study presents a comparative analysis of Spain and Portugal, examining the regulatory frameworks, educational policies, and institutional practices related to the support of students with ASD, with a particular focus on teacher training and evaluation as key elements of inclusion. Using a qualitative and documentary methodology based on a review of legislative, academic, and institutional sources, significant similarities and differences between the two countries are identified. The results show that Portugal has achieved greater coherence between legislation, pedagogical guidance, and teacher support, consolidating an inclusive education model based on Universal Design for Learning (UDL) and formative teacher evaluation. In Spain, although the LOMLOE (2020) reinforces the commitment to equity, its practical application depends on regional management and resource allocation, leading to territorial disparities. The study concludes that teacher quality is the central element that links inclusive policies, vocational training, and educational practice.Keywords: teaching quality; comparative education; Spain; educational inclusion; Portugal; Autism Spectrum Disorder.